Low molecular weight polyethylenimine-conjugated gold nanospheres: a platform for selective gene therapy controlled by near-infrared light. (March 2017) - Liu, Fei; Kong, Fen-fen; Li, Qing-po; Yuan, Hong; Du, Yong-zhong; Hu, Fu-qiang; Sun, Ji-hong; You, Jian
Aim: Whether PEI2k -HAuNS could promote gene transfection efficiency controlled by near-infrared (NIR) light.Materials & methods: This safe nonviral gene delivery system was obtained by conjugating low molecular weight (2 kDa) polyethylenimine (PEI) onto hollow gold nanospheres (PEI2k -HAuNS). Upon NIR laser irradiation, there was a conspicuous increase both in the in vitro and in vivo transfection achieved by the nanocomplexes. Furthermore, a plasmid encoding the tumor suppressor TP53 (pTP53) was applied to test antitumor activity.Results: The enhanced gene transfection efficiency and therapy of PEI2k -HAuNS were achieved via the mediation of an NIR laser compared with the other treatments in vitro and in vivo .Conclusion: The application of NIR laser irradiated PEI2k -HAuNS can be used as a promising gene delivery systems in vitro and in vivo .